2016
DOI: 10.1002/ird.2020
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of an Emitter Clogging Control Strategy for Drip Irrigation with Reclaimed Water

Abstract: Controlling emitter clogging by reducing clogging substances is commonly used nowadays, but it is merely applied in clogged emitters, so establishing a convenient and pre‐treated emitter clogging control strategy is essential. In this paper, four types of non‐pressure‐compensating emitters were selected for a drip irrigation experiment using reclaimed water. Furthermore, suspended particles' components in reclaimed water treated with four technologies were tested, and then their components' relations with emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…These results confirm those obtained by Bourziza et al (2017) who found that high salinity in irrigation water increases the risk of dripper clogging. Also, Zhou et al (2016), and Szekut et al (2020) found in their research work that suspended solids present in the water accentuated the clogging of drippers.…”
Section: Resultsmentioning
confidence: 91%
“…These results confirm those obtained by Bourziza et al (2017) who found that high salinity in irrigation water increases the risk of dripper clogging. Also, Zhou et al (2016), and Szekut et al (2020) found in their research work that suspended solids present in the water accentuated the clogging of drippers.…”
Section: Resultsmentioning
confidence: 91%
“…Adin and Mollie (1991) and Camp (1998) found that emitters with a shorter and wider flow path had better anti-clogging ability. Bo et al (2014) experimentally investigated the clogging of drip irrigation emitters using reclaimed water. These emitters differed simply in the depth of the flow path, which was 0.75, 0.83, 1.01, and 1.08 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%